Strategy Orientation, Use Of Online Media – Social Media, Business Performance During The Covid-19 Pandemic - Antonius Singgih Setiawan; Cheryna Natalie; Junaidi (Jurnal Manajemen, 2022)
The COVID-19 pandemic crisis has disrupted the movement of MSME actors in running their businesses. The use of online media – especially social media – is considered by many to be the main impact of a business strategy orientation that focuses on competitive and innovative strategies to improve business performance. For this reason, this study aims to prove whether there is an influence between strategic orientation on the use of online media and social media and to prove the use of online media and social media on MSME business performance in the city of Palembang. To test the hypothesis, a sample of 160 (80percent) MSME entrepreneurs in Palembang were polled, and Structural Equation Modeling (SEM) analysis of Partial Least Squares (PLS) was performed using Warp PLS software version 5.0. The results showed that the strategic orientation of MSME entrepreneurs in the city of Palembang had a positive effect on the use of online media and social media in their business activities. The research findings also show that the use of online media, particularly social media, has a positive effect on the achievement of their business performance during the COVID-19 pandemic.